Incidence of filled antidepressant prescriptions among people with newly diagnosed diabetes and its interaction with occupational status within the working population of Denmark 1996–2010. Issue 4 (August 2018) - Cleal, Bryan; Panton, Ulrik Haagen; Willaing, Ingrid; Holt, Richard
Highlights: Filled antidepressant prescription incidence peaked at ≤1 year diabetes diagnosis. Low socioeconomic status was a risk factor for filling antidepressant prescription. Female gender was general risk factor for filling antidepressant prescriptions. Diabetes duration modified risks for filling antidepressant prescription. Abstract: Aims: People with diabetes have heightened levels of depressive symptoms, but less is known about the development of these symptoms in relation to diabetes duration. In this study, we examined the use of prescribed antidepressants in the first five years after diagnosis of diabetes among the working-age population in Denmark. Methods: All Danish adults aged 18–54 years, diagnosed with diabetes in the study period were included. Diabetes status and purchase of prescription antidepressants were obtained from validated population registers. Data analysis focused on filled antidepressant prescriptions at ≤1 and ≤5 years from diagnosis with diabetes. Results: 35, 677 people diagnosed with diabetes were included in the study. At ≤1 year post-diagnosis, 2.6% had filled antidepressant prescriptions. At ≤5 years, this figure rose to 10.4%. Overall, both female gender and lower socioeconomic status were associated with higher incidence of filled antidepressant prescriptions. Diabetes duration modified the degree of differences between men and women and socioeconomic strata. Conclusion: Diagnosis with diabetes immediately impacts mental wellbeing, with higher rates of filled antidepressant prescriptions in the first year after diagnosis. People of working age diagnosed with diabetes face specific challenges and addressing such challenges would enhance patient experiences. Focus on mental health in the clinical encounter with people newly diagnosed with diabetes is warranted and important.